تأثير مسحوق بعض الطحالب البحرية السورية في نمو نبات البندورة في ظروف مختلفة (المختبر والبيت البلاستيكي) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
This study investigated the effect of dry powder of three types of Syrian marine algae Ulva  fasciata , Codium tomentosum (green algae) and Hypnea musciformis (red algae) In the growth of tomato Plants Solanum lycopersicum concentrations (2, 4 and 6) g per 1kg soil and control sample without additives, The study was conducted in both the laboratory and the green house. The comparison was done in the number of leaves, plant length and date of flowering. The results showed that the date of flowering in  the green house plants began in the second week in the plants treated with the powder H. musciformis at the concentration of 2g / Kg ,while the control samples after three weeks also The maximum number of leaves was 12 leaves at 2g / Kg concentration of U. fasciata powder with increase 3 leaves from the control sample. The highest plant length was 27.4cm at 2g / Kg concentration of H. mociformis, 6.4cm higher than the control sample . In the laboratory plants the date of flowering was after two months and half of the cultivation in the plants treated with the powder of H. musciformis at the concentration 2g / Kg and control samples after three months and the largest number of leaves 14 at the concentration 2g / Kg of powder U. fasciata with increase 3 leaves from the control sample, The highest plant length was 44 cm at the same concentration , 10cm higher than the control sample , which reached 34 cm in length. تم في هذا البحث دراسة تأثير المسحوق الجاف لثلاثة أنواع من الطحالب البحرية السورية Ulva fasciata (طحالب خضراء) و tomentosum Codium (طحالب خضراء) و musciformis Hypnea (طحالب حمراء) في نمو شتلات البندورة lycopersicum Solanum صنف (قصبية) بتراكيز (2 , 4 , 6) g لكل 1kg تربة و العينة الشاهدة دون إضافات حيث أجريت الدراسة في كل من المختبر و البيت البلاستيكي و تمت المقارنة من حيث عدد الأوراق و طول النبات و موعد الإزهار. أظهرت نتائج نباتات البيت البلاستيكي أن موعد الإزهار بدأ في الأسبوع الثاني بعد الزراعة لدى العينات المعاملة بمسحوق musciformis H. بتركيز 2g/Kg , بينما كان لدى العينات الشاهدة كان بعد ثلاثة أسابيع من الزراعة وبلغ أكبر عدد للأوراق 12) ورقة) عند التركيز 2g/Kg من مسحوق طحلب U. fasciata بزيادة 3 أوراق عن العينة الشاهدة و كانت أعلى قيمة لطول النبات 27.4cm عند التركيز 2g/Kg من مسحوق طحلب musciformis .H بزيادة 6.4cm عن العينة الشاهدة. أما في نباتات المختبر كان موعد الإزهار بعد شهرين و نصف من الزراعة لدى العينات المعاملة بمسحوق musciformis H. بتركيز 2g/Kg أما العينات الشاهدة كان بعد ثلاثة أشهر و بلغ أكبر عدد للأوراق  14)ورقة) عند التركيز 2g/Kg  من مسحوق طحلب U. fasciata بزيادة 3 أوراق عن العينة الشاهدة , و كذلك كانت أعلى قيمة لطول النبات 44cm عند التركيز ذاته بزيادة 10cm عن العينة الشاهدة و التي بلغ فيها الطول 34cm.